Persistent Itsenko-Cushing’s disease with no remission after two surgical treatments: a clinical case - Elizaveta V. Osipova; Polina A. Smirnova; Valeria D. Soldatova; Anna S. Dzyuba; Maria G. Pavlova (Consilium Medicum)
Itsenko-Cushing’s disease (ICD) is a rare neuroendocrine disease caused by hyperproduction of adrenocorticotropic hormone (ACTH) by pituitary adenoma, leading to a persistent increase in cortisol levels and the development of endogenous hypercorticism. Without treatment, ICD leads to severe complications and significantly reduces life expectancy. Transsphenoidal adenomectomy remains the “gold standard” of treatment, but a significant proportion of patients experience persistence or recurrence of the disease, requiring the use of alternative treatments. This paper presents a clinical case of a patient H., 62 years old, with confirmed ACTH-dependent hypercorticism. The diagnosis was made in 2023 based on the following tests: cortisol level in a nocturnal suppression test with 1 mg of dexamethasone – 458 nmol/L, salivary cortisol at 23:00 – 10.37 nmol/L, daily urinary cortisol excretion – 200 μg/day, ACTH – 14.7 pmol/L. Magnetic resonance imaging showed a pituitary microadenoma. A transsphenoidal adenomectomy was performed; however, remission was not achieved. Ketoconazole therapy was administered, with clinical improvement, but the patient subsequently discontinued the drug on her own. Upon follow-up examination a year later, the persistence of ICD was confirmed (salivary cortisol at 23:00 – 10.5 nmol/L, daily urinary cortisol excretion – 475.2 μg/day, ACTH – 49.8 pg/mL), magnetic resonance imaging showed signs of a residual pituitary tumor. Repeated transsphenoidal adenomectomy was performed, but remission was not achieved again. At follow-up, clinical and laboratory signs of hypercorticism and the patient’s severe condition persisted. Due to the ineffectiveness of surgical treatment, the patient was referred for stereotactic radiosurgery. The management of patients with a persistent or recurrent ICD remains clinically challenging due to the lack of a universal, highly effective, and safe therapeutic approach. The treatment strategy is determined individually, considering the severity of hypercorticism, the presence of complications, the disease prognosis, and the availability of therapies.